2023
DOI: 10.3390/ijms241310638
|View full text |Cite
|
Sign up to set email alerts
|

Fads2b Plays a Dominant Role in ∆6/∆5 Desaturation Activities Compared with Fads2a in Common Carp (Cyprinus carpio)

Abstract: Highly unsaturated fatty acids (HUFAs) are essential for mammalian health, development and growth. However, most mammals, including humans, are incapable of synthesizing n-6 and n-3 HUFAs. Fish can convert C18 unsaturated fatty acids into n-6 and n-3 HUFAs via fatty acid desaturase (Fads), in which Fads2 is a key enzyme in HUFA biosynthesis. The allo-tetraploid common carp theoretically encode two duplicated fads2 genes. The expression patterns and desaturase functions of these two homologous genes are still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…This result suggests that MulFadsB transcripts in the eggs and early larvae are maternally derived rather than endogenously expressed [42]. A similar maternal expression pattern of Fads has also been reported in Danio rerio [42], Common Carp Cyprinus carpio [38], and noble scallop C. nobilis [40]. While the MulFadsA transcript was low at the early developmental stage, it increased dramatically from blastula stages to juvenile stages, indicating that ∆5 Fads may be a critical enzyme in the biosynthesis of PUFAs that are needed in normal development during the early stages in mollusks [40] and other animals [42].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This result suggests that MulFadsB transcripts in the eggs and early larvae are maternally derived rather than endogenously expressed [42]. A similar maternal expression pattern of Fads has also been reported in Danio rerio [42], Common Carp Cyprinus carpio [38], and noble scallop C. nobilis [40]. While the MulFadsA transcript was low at the early developmental stage, it increased dramatically from blastula stages to juvenile stages, indicating that ∆5 Fads may be a critical enzyme in the biosynthesis of PUFAs that are needed in normal development during the early stages in mollusks [40] and other animals [42].…”
Section: Discussionsupporting
confidence: 75%
“…Typical front-end desaturases of animals in the biosynthesis of LC-PUFAs include Δ4, Δ5, Δ6, and Δ8 fatty acid desaturases. Various Fads genes demonstrating a range of desaturation activity, such as Δ4, Δ5, Δ6, Δ8, Δ5/6, and Δ6/8, have been identified in mammals and teleost fish [ 30 , 34 , 35 , 36 , 37 , 38 ]. In addition, a series of studies have demonstrated that Fads with ∆5, Δ6, or Δ8 activity appear to be widely distributed among mollusks, including cephalopods [ 12 , 39 ], gastropods [ 13 ], and bivalves [ 14 , 15 , 19 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of PUFAs in fish is a process in which LA and ALA are used as substrates to synthesize PUFA through continuous desaturation and elongation reactions. This synthesis pathway is mainly catalyzed by fatty acid desaturase (Fads) that catalyzes the desaturation reaction and elongase of very-long-chain fatty acids (Elovl) that catalyze the carbon chain extension reaction [7,8]. The elovl gene family, which encodes the synthesis of C18 or longer chain fatty acids [9], is a rate-limiting enzyme in these reaction steps [10], playing a crucial role in fatty acid synthesis [11].…”
Section: Introductionmentioning
confidence: 99%